Mean and Seasonal Circulation of the Eastern Chukchi Sea From Moored Timeseries in 2013–2014. Issue 5 (17th May 2021) - Tian, Fei; Pickart, Robert S.; Lin, Peigen; Pacini, Astrid; Moore, G. W. K.; Stabeno, Phyllis; Weingartner, Thomas; Itoh, Motoyo; Kikuchi, Takashi; Dobbins, Elizabeth; Bell, Shaun; Woodgate, Rebecca A.; et al.
Abstract: From late‐summer 2013 to late‐summer 2014, a total of 20 moorings were maintained on the eastern Chukchi Sea shelf as part of five independent field programs. This provided the opportunity to analyze an extensive set of timeseries to obtain a broad view of the mean and seasonally varying hydrography and circulation over the course of the year. Year‐long mean bottom temperatures reflected the presence of the strong coastal circulation pathway, while mean bottom salinities were influenced by polynya/lead activity along the coast. The timing of the warm water appearance in spring/summer is linked to advection along the various flow pathways. The timing of the cold water appearance in fall/winter was not reflective of advection nor related to the time of freeze‐up. Near the latitude of Barrow Canyon, the cold water was accompanied by freshening. A one‐dimensional mixed‐layer model demonstrates that wind mixing, due to synoptic storms, overturns the water column resulting in the appearance of the cold water. The loitering pack ice in the region, together with warm southerly winds, melted ice and provided an intermittent source of fresh water that was mixed to depth according to the model. Farther north, the ambient stratification prohibits wind‐driven overturning, hence the cold water arrives from the south. The circulation during the warm and cold months of the year is different in both strength and pattern. Our study highlights the multitude of factors involved in setting the seasonal cycle of hydrography and circulation on the Chukchi shelf. Plain Language Summary: From late‐summer 2013 to 2014, a total of 20 moorings were maintained on the eastern Chukchi Sea shelf, north of Bering Strait, as part of five independent field programs. We analyze these data to obtain a broad view of the mean water conditions and circulation, as well as the dominant variability over the course of the year. The year‐long mean bottom temperatures reflected the presence of the strong current adjacent to the Alaskan coast, while the mean bottom salinities were influenced by the frequent presence of persistent openings in the sea ice, which result in the formation of salty water when the ice re‐freezes. The appearance of warm water across the shelf in spring/summer was mainly dictated by the speed of the water from south to north. However, the appearance of cold water in fall/winter was not reflective of this. Using a simple model, it is demonstrated that storm events mixed cold and fresh surface water to the bottom on the mid‐shelf. Farther to the northeast, this does not happen because the water is more stratified, and this prohibits such wind mixing. Finally, it is shown that the circulation during the warm and cold months of the year is different in both strength and pattern. Key Points: The appearance of warm water across the Chukchi shelf in spring is dictated by advection, but the appearance of cold water in the fall is not Wind mixing from autumn storms brings cold, fresh water to depth on the mid‐shelf, but strong stratification prohibits this farther north The circulation during the warm and cold months of the year is different in both strength and pattern